Antidepressant Use Is Associated With an Increased Risk of Developing Microbleeds. Issue 1 (January 2016) - Akoudad, Saloua; Aarts, Nikkie; Noordam, Raymond; Ikram, M. Arfan; Tiemeier, Henning; Hofman, Albert; Stricker, Bruno H.; Vernooij, Meike W.; Visser, Loes E.
Abstract : Background and Purpose—: Serotonin-specific antidepressants may increase the risk of adverse bleeding events. In a previous cross-sectional study, we did not observe an association between antidepressant use and presence of subclinical cerebral bleedings. In this study, we investigated longitudinally whether antidepressant use is associated with an increased risk of new subclinical cerebral microbleeds. Methods—: In total, 2559 participants aged ≥45 years of the population-based Rotterdam Study, all without microbleeds at baseline, underwent baseline and repeat brain magnetic resonance imaging between 2005 and 2013 (mean time interval, 3.9 years; SD, 0.5) to determine the incidence of microbleeds. Antidepressant use (yes versus no) was assessed between baseline and follow-up scan. In additional analyses, antidepressants were classified as low, intermediate, or high affinity for the serotonin transporter, and alternatively as selective serotonin reuptake inhibitors or non-selective serotonin reuptake inhibitors. We used multivariable logistic regression models to investigate the association of antidepressants with incident microbleeds. Results—: Antidepressant use was associated with a higher cerebral microbleed incidence (odds ratio, 2.22; 95% confidence interval, 1.31–3.76) than nonuse. When stratified by affinity for the serotonin transporter, intermediate serotonin affinity antidepressant use was associated with an increased risk of developing microbleeds (odds ratio, 3.07; 95% confidence interval, 1.53–6.17). Finally, selective serotonin reuptake inhibitor and non-selective serotonin reuptake inhibitor use were both associated with increased microbleed incidence. Conclusions—: Antidepressant use was associated with an increased risk of developing microbleeds. Our results may support findings from previous clinical studies about increased intracranial and extracranial bleeding risk in antidepressant users.